Detecting genuine multipartite entanglement of pure states with bipartite correlations - Markiewicz, Marcin (2013)
Monogamy of bipartite correlations leads, for arbitrary pure multiqubit states, to simple conditions able to indicate various types of multipartite entanglement by being capable of excluding the possibility of k separability.